Meningkatkan Aktivitas Belajar Digital Siswa Melalui Model Pembelajaran Berbasis Masalah Pada Mata Pelajaran IPA Kelas V MIN 15 Stabat T.A 2019/2020 - Gita Dwi Wardani (Program Studi PGSD Kampus UPI di Serang, 2021)
The purpose of this study was to increase students' online learning activities by using a problem-based learning model in science subjects with material on diseases attack human respiratory organs in class V MIN 15 Langkat T.A 2019/2020. This type of research is